Pengembangan E-LKPD Berbasis Website Wizer.Me Materi Teks Cerita Fantasi Kelas VII - Fransiskus Dwi Anggoro (Universitas Palangka Raya, 2023)
This study aims to describe the stages of developing E-LKPD based on the Wizer.me Website on fantasy story text material for class VII and the form of E-LKPD based on the Wizer.me Website on fantasy story text material for class VII. This research uses the Research and Development (R&D) method with the Borg and Gall model, which uses 6 stages according to the needs, abilities and scope of the research. The results of the study show that 1) the stages of developing E-LKPD based on the Wizer.me Website for fantasy story text material start from the potential and problem analysis stages with unstructured interviews with teachers and analysis of the LKPD used by the teacher during learning. The next stage is needs analysis, product design stage, product validation stage carried out by material expert validators and media design expert validators. The score obtained was 86.11% from the material expert validator, and 83.33% from the media design expert validator. Based on the results of this assessment, it can be concluded that the E-LKPD based on the Wizer.me Website, fantasy story text material for class VII